Assessing the health hazard originated via pesticide chemicals in human through rabbit model in agricultural production system in Bangladesh - Amir Hossan Shaikat; Shahneaz Ali Khan; Mohammed Ashif Imtiaz; Md Ridoan Pasha; Jabin Sultana; Arfanul Saif; Mohammad Rashedul Alam (BMC, 2022)
Abstract Background The use of chemical pesticides in developing countries like Bangladesh and their impacts on human health and food security is a global concern. Bangladesh is an agricultural dependent country for the growing population demand for food security and food safety. We conduct this study to assess public health threats of commonly utilised pesticides including malathion and nitrobenzene in female rabbit model. Methods Thirty New Zealand White healthy rabbit was divided randomly into three groups; and subjected to distilled water as control, malathion@ 5 mg/kg body weight and nitrobenzene@ 5 mg/kg body i.p daily for the next 15 days. Hematology, serum biochemistry and hormonal assay were performed. Results Red blood cell (RBC) concentrations (TEC, Hb, PCV%) were reduced in rabbits exposed to malathion and nitrobenzene. The neutrophil and eosinophil percentage were increased in the malathion and nitrobenzene exposed juvenile rabbit group. We found that serum aspartate aminotransferase (AST) and creatinine were increased in the nitrobenzene exposed group in infants, whereas malathion exposure increased serum alanine aminotransferase (ALT). In contrast, the juvenile group exposed to malathion increased the ALT level. There was no change in AST or creatinine levels in juvenile rabbits exposed to malathion or nitrobenzene. Serum estradiol levels were significantly lower in rabbits exposed to malathion and nitrobenzene. Serum testosterone concentration was increased in juvenile rabbits exposed to malathion and nitrobenzene, but progesterone was decreased in malathion exposed juvenile rabbits. Conclusion However, this study highlights the importance of rigorous monitoring and testing of agricultural products. In addition, strengthen research and extension in the fields of agro economy, organic farming, local universities and farmer associations.